Correlation Between Body Condition Score with Reproductive Disorders, Reproductive Performance, and Estrus Performance in Beef Cattle - Afif, Mohammad Faiq Naufal; Samsudewa, Daud; Muktiani, Anis (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
ABSTRACT. The aim of the study is to determine the relationship between body condition score with reproductive disorders, reproductive performance and estrus performance in beef cattle. Sixty beef cattle were used in this research. Body condition score (BCS), reproductive disorders, reproductive performance and estrus performance were measured in this research. Data were analyzed using correlation and simple linear regression. The results in this research showed that the relationship between BCS and reproductive disorders, condition of vulva, behavior, intensity of mucus and uterine erection had no significant effect (p 0.05) with the value of the regression equation and the correlation coefficient respectively Y = 4,964 - 0,57X and 0,12; Y = 2.235 + 0.14X and 0.26; Y = 1.788 + 0.89X and 0.153; Y = 2.343 - 0.12X and 0.23; Y = 1.352 + 0.1X and 0.198. BCS with Service per conception, Days open, Conception rate and Estrus post partum showed significant results (P 0.05) with the value of the regression equation and the correlation coefficient Y=2.266-0.201X and 0.35; Y = 107.35-3.56X and 0.33 and Y = 96.923-4.385X and 0.499; Y = 87,891 - 4,189X and 0,508. The conclusion of this study is that Body condition score has a significant effect on Service per conception, Days open, Conception rate and Estrus post partum.